The Guenons: Diversity and Adaptation in African Monkeys - Glenn, Mary E.; Cords, Marina. (Developments in Primatology: Progress and Prospects, 2002)
It has been twelve years since a work relating to the long-tailed African monkeys known as the guenons has been published and fifteen years have passed since the last major scientific symposium was held that was solely dedicated to current research on members of this monkey group living in the wild. Since that time, new guenon species and subspecies have been discovered, previously unstudied guenon species have become the subject of long-term research projects, and knowledge of the more well-known guenon species has greatly increased. This volume presents novel information and keen insight on research previously studied and newly discovered. A wide range of topics related to guenon biology is presented, including evolution, taxonomy, biogeography, reproductive physiology, social and positional behavior, ecology, and conservation. Composed of 26 chapters compiled by 47 authors, many of whom are young investigators in their field, The Guenons: Diversity and Adaptation in African Monkeys provides a valuable resource for researchers and scientists in the fields of anthropology, primatology, zoology, and conservation biology.